Microbial Contamination in Urban Marine Sediments: Source Identification Using Microbial Community Analysis and Fecal Indicator Bacteria - Ellinor M. Frank; Carolina Suarez; Isabel K. Erb; Therese Jephson; Elisabet Lindberg; Catherine J. Paul (Microorganisms)
We investigated the presence of the fecal indicator bacteria Escherichia coli, and other taxa associated with sewage communities in coastal sediments, near beaches with reported poor bathing water quality, focusing on the influence of effluent from a local wastewater treatment plant (WWTP) and combined sewer overflows (CSO). Using a three-year dataset, we found that treated wastewater effluent is a significant source of sewage-associated taxa and viable E. coli in the sediments and that no seasonal differences were observed between spring and summer samples. CSO events have a local and temporary effect on the microbial community of sediments, distinct from that of treated wastewater effluent. Sediments affected by CSO had higher abundances of families Lachnospiraceae, Ruminococcaceae, and Bacteroidaceae. Sewage releases may also impact the natural community of the sediments, as higher abundances of marine sulfur-cycling bacteria were noticed in locations where sewage taxa were also abundant. Microbial contamination at locations distant from known CSO and treatment plant outlets suggests additional sources, such as stormwater. This study highlights that while coastal sediments can be a reservoir of E. coli and contain sewage-associated taxa, their distribution and potential origins are complex and are likely not linked to a single source.